Community tensions, participation, and local development: Factors affecting the spatial embeddedness of anaerobic digestion in Poland and the Czech Republic. (September 2019) - Chodkowska-Miszczuk, Justyna; Martinat, Stanislav; Cowell, Richard
Highlights: Embeddedness of anaerobic digestion plants in the life of rural communities is surveyed. Questionnaire surveys and a set of interviews with stakeholders were conducted. AD plants have the specific qualities of being grounded in local economies and relying on local resources. Visiting an AD plant significantly (and positively) affects the opinion of local publics about AD. Abstract: Anaerobic Digestion plants (AD plants) are an important part of energy transition towards low-carbon rural economies in Central European countries. However, their benefits in making rural spaces more energy sustainable and energy self-sufficient are frequently questioned. In our paper, we strive to deepen our understanding of the level of embeddedness of two modes of operation of AD plants (AD on-farm, AD off-farm) in cases of Poland and the Czech Republic. We evaluate the pros and cons of both modes and assess their importance for the local rural development and energy transition through the lens of their embeddedness in the life of rural communities. Through questionnaire surveys in two municipalities (Buczek in Poland, Stonava in the Czech Republic, n = 232) and a set of expert interviews (19) with local and regional stakeholders, we have found that AD plants are specific rural enterprises as they usually rely on local biomass resources and are generally more grounded in the local economy and in local social structures than other enterprises. We also discovered that both types of AD plants investigated create significant (but varied) linkages with local stakeholders. The awareness of ADs among local population is high and significantly influenced by previous visits to the AD plant. By providing jobs and organizing local events for the local population operators of AD plants create space for their deeper acceptability and their embeddedness into the life of rural communities, however, site-specificity and local socio-cultural contexts must be also considered.